Photoinduced Copper‐Catalyzed Asymmetric C(sp3)−H Alkynylation of Cyclic Amines by Intramolecular 1, 5‐Hydrogen Atom Transfer. Issue 34 (13th July 2022) - Guo, Rui; Xiao, Haijing; Li, Sijia; Luo, Yixin; Bai, Jiahui; Zhang, Mengzhen; Guo, Yinlong; Qi, Xiaotian; Zhang, Guozhu
Abstract: The development of a mild and general method for C(sp 3 )−H functionalization of cyclic amines has been an ongoing challenge. In this work, we describe the copper‐catalyzed enantioselective C(sp 3 )−H alkynylation of unactivated cyclic 2‐iodo‐benzamide under photo‐irradiation by intramolecular 1, 5‐hydrogen atom transfer (HAT). The employment of a new bisoxazoline diphenylamine ligand, in conjunction with 1, 1′‐bi‐2‐naphthol, which significantly improved the reduction potential of the copper complex, was the key to success of this chemistry. Mechanistic and computational studies supported that the new copper complex served the dual role as a photoredox and coupling catalyst, the reaction went through a radical process, and the intramolecular 1, 5‐HAT process was involved in the rate‐limiting step. Apart from the broad substrate scope including unprecedented benzocyclic amines, this method also showed excellent diastereoselectivity in 2‐monosubstituted cyclic amines via substrate control. Abstract : The copper‐catalyzed enantioselective C(sp 3 )−H alkynylation of cyclic 2‐iodo‐benzamide under photo‐irradiation by intramolecular 1, 5‐hydrogen atom transfer has been developed. The employment of a new bisoxazoline diphenylamine ligand and 1, 1′‐bi‐2‐naphthol, which significantly improved the reduction potential of the new copper complex that served the dual role as a photoredox and coupling catalyst, was the key to success of this chemistry.